SPONTANEOUS STRAIN VARIATIONS THROUGH THE LOW TEMPERATURE PHASE TRANSITIONS OF DEUTERATED LAWSONITE - Carpenter M.A.; Meyer H.W.; Sondergeld P.; Marion S.; Knight K.S. (My University, 2003)
High resolution neutron powder diffraction has been used to determine lattice parameter variations of deuterated lawsonite across the Cmcm ↔ Pmcn and Pmcn ↔ P21cn phase transitions, in the temperature interval 1.6–505 K. The variations are reversible through heating and cooling cycles. Strain analysis, based on a displacive model of the transitions with saturation temperatures to describe the temperature-independent behavior as T → 0 K, shows that the data are consistent with a tricritical transition at 271 ± 2 K and a second-order transition at 155 ± 1 K. Comparisons with strains from published dilatation data for a natural (hydrogenated) sample highlight aspects of the transitions that are most dependent on the behavior of protons in the structure. Replacing H by D causes the low temperature transition point to be increased by ~27 K and an anomaly in the strain evolution of the Pmcn transition to increase from ~225 to ~250 K. The transition point of the high-temperature transition remains the same within ± ~2 K. We conclude that proton ordering and displacive contributions are both important in the 271 K transition, though with the displacive component providing the initial symmetry-breaking mechanism. Structural changes that are more dependent on the behavior of H or D become important ~20–50 K below this. Strains for the Pmcn ↔ P21cn transition are consistent with a transition driven by a single order parameter. The data are used to determine values for strain/order parameter coupling coefficients for calculation of elastic anomalies due to the phase transitions.